2021
DOI: 10.1177/0272684x211025438
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Status and Related Factors among Medical Students: A Cross-Sectional Study in Western Iran

Abstract: Background In recent years, Internet and social media technology use have emerged as an integral tool of human society, and the evolution of technological integration, cyberspace, and web-technology has become a common practice in educational institutions. Internet usage among students has played an indispensable role in learning behavior; however, the excessive usage of the internet and social media leads to internet addiction. This original study has performed a focalized scrutiny on revealing relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 54 publications
(94 reference statements)
4
37
0
Order By: Relevance
“…The literature evidenced that various elements help promote and inhibit life satisfaction of individuals: a specific note of this study described that spirituality and religiosity play an indispensable role as religions help provide psychological resources, which have a positive linkage to psychological wellbeing (Barreto et al, 2015;Taufik et al, 2021;Wang et al, 2021). Internet use and innovative strategies amid COVID-19 pandemic provide updated information for better mental health solution (Jafari et al, 2010;Azizi et al, 2021;Khazaie et al, 2021). The scientific community reported that religion is one of the vital factors of the mental health individuals in the COVID-19 crisis, and religious beliefs provide mental relaxation to patients (Fardin, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…The literature evidenced that various elements help promote and inhibit life satisfaction of individuals: a specific note of this study described that spirituality and religiosity play an indispensable role as religions help provide psychological resources, which have a positive linkage to psychological wellbeing (Barreto et al, 2015;Taufik et al, 2021;Wang et al, 2021). Internet use and innovative strategies amid COVID-19 pandemic provide updated information for better mental health solution (Jafari et al, 2010;Azizi et al, 2021;Khazaie et al, 2021). The scientific community reported that religion is one of the vital factors of the mental health individuals in the COVID-19 crisis, and religious beliefs provide mental relaxation to patients (Fardin, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…The different waves of the current pandemic have created a massive burden and caused health risks for human beings, leading to an increase in the usage of social media applications as people seek the latest news about preventive measures against the COVID-19 disease. People look for precise and correct information related to their health, which has led to more use of platforms of media technologies to stay connected with family members, peers, and friends (83)(84)(85)(86). People seek accurate information related to viral disease, and social media use has helped people find public communication to follow preventive measures (87).…”
Section: Social Media Use and Health Behaviormentioning
confidence: 99%
“…They also pointed out that the integration of education and AI technology can not only improve the teaching efficiency of teachers but also attract students to better integrate into the classroom. Moreover, the system design of AI education in the future is likely to model the learning situation of students, improving the current teaching methods to provide students with a better learning environment (Khazaie et al, 2021 ; Taufik et al, 2021 ). Other experts have proposed that traditional learning methods have to be upgraded and transformed with the integration of education and AI, which can not only provide a good learning experience for learners but also provide related researchers with more basis for improvement in learning principles (D'Mello, 2016 ; Nye, 2016 ).…”
Section: Discussionmentioning
confidence: 99%